Three-dimensional high-resolution crystallographic observation of the entire volume of microstructurally small fatigue cracks in Ni-Co based superalloy. (1st January 2023) - Nishikawa, Hideaki; Furuya, Yoshiyuki; Osada, Toshio; Kawagishi, Kyoko; Hara, Toru
Abstract: The crystallographic features of microstructurally small fatigue cracks (MSFCs) in a Ni-Co-based superalloy were analyzed by using a Xe plasma focused ion beam scanning electron microscope (PFIB-SEM) system in conjunction with electron backscatter diffraction (EBSD) analysis. The crystallographic orientation of the three-dimensional (3D) fatigue crack growth path was successfully observed using a large-volume, high-resolution 3D image. The major parts of the crack surface were close to the {111} slip plane. Our results indicated that the Mode II fatigue crack growth mechanism is locally more predominant than the general blunting-resharpening Mode I fatigue crack growth mechanism, not only in the Stage I region but also in the larger part of the Stage II region of MSFC growth process. Graphical abstract: Image, graphical abstract